Beyond The Classroom: A Backstage Pass of How a University Runs - (:unkn) unknown (Kansas State University. K-State First., 2015)
A poster promoting the presentation "A Backstage Pass of How a University Works" at Kansas State University, hosted by Dr. Pat Bosco, Vice President of Student Life and Dean of Students, on February 17, 2015 at 7 PM.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Posters